Conserved pigment pathways underpin the dark insectiform floral structures of sexually deceptive Chiloglottis (Orchidaceae) - Wong, Darren C. J.; Perkins, James; Peakall, Rod (Frontiers in Plant Science, 2022)
Sexually deceptive plants achieve pollination by enticing specific male insects as pollinators using a combination of olfactory, visual, and morphological mimicry. The sexually deceptive orchid genus Chiloglottis is comprised of some 30 species with predominantly dull green-red flowers except for the dark insectiform calli/callus structure from the labellum lamina. This unique structure mimics the female of the pollinator and potentially enhances the visibility of the mimic. However, the chemical and genetic basis for the color of these structures remains poorly understood across the genus. The goal of this study was to investigate the flower color biochemistry and patterns of gene expression across the anthocyanin and flavonol glycoside biosynthetic pathway within the calli structures across the three distinct clades of Chiloglottis (Formicifera, Reflexa, and Valida) using chemical and transcriptome analysis. Our phylogenomic analysis confirmed the close sister relationship between the Reflexa/Formicifera clades and reaffirms the basal position of the Valida clade. Additionally, the biochemical basis of the dark calli/callus structures is conserved across the genus. Nonetheless, the proportion of methoxylated anthocyanin and flavonol glycoside derivatives and the mean gene expression levels appear to differentiate the Reflexa and Formicifera clades from the Valida clade. In future studies, it will be of interest to tease apart the role of phylogeny, environment, pollinators, and other factors as potential drivers of the observed biochemistry and gene expression differences. It will also be important to characterise the function of candidate genes such as DFR, LDOX, and FLS in this fascinating case of flower color mimicry.